MENINGKATKAN SEKTOR LOGISTIK DALAM PENDISTRIBUSIAN DAN PEMASARAN PRODUK DARI USAHA MIKRO KECIL DAN MENENGAH (UMKM) - Annisa Hasanah; Rafael Permana; Sheila Sulistiawati; Risandi Yusuf Fadanrangi; Sonya Ritta Sitinjak (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2024)
The importance of micro, small, and medium-sized enterprises (MSMEs) in the economic developmentofIndonesiaissignificant.Theprimaryfocusisonenhancingthelogisticssectorin the marketing and distribution of MSME products. In the context of globalization, MSMEs have become a positive trend due to their substantial contribution to a country's Gross Domestic Product (GDP). Empowerment programs for MSMEs, including aspects of marketing and distributionlogistics,havebecomecrucial.Theseprogramsarebasedonprinciplessuchas increasingself-reliance,cohesion,developingentrepreneurshipbasedonregionalpotential,and improving competitiveness. The goal of the MSME sector development program is to create a balanced economic structure, strengthen MSMEs, and enhance their role in regional development and poverty alleviation. It can be concluded that the lack of understanding of logistics in the distribution of MSME products highlights the need for the socialization and marketingofthelogisticsindustrytoexpandthemarket.Innovation,creativityinmarketing,and theutilizationoftechnologyarekeyfactors.Inthelogisticsindustry,effectiveunderstandingand training are necessary to improve satisfaction and reach a broader market. In summary, the improvement of the logistics sector can facilitate the marketing of MSME products at the nationalandinternationallevels,helpMSMEscompeteintheglobalmarket,andpromotemore equitable economic growth.